CORROSION OF METALS AND NEW INNOVATIVE METHODS OF THEIR PREVENTION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the purpose of corrosion protection, the causes of metal corrosion, the advantages and disadvantages of various methods of protecting metal structures from electrochemical corrosion were considered. In order to make metal products last longer, the problem of corrosion from electrochemical corrosion is described in detail based on experiments.